Lipocalin-2 Variants and Their Relationship With Cardio-Renal Risk Factors - Li, Dahui; Li, Haoyun; Bauer, Carlie; Hu, Yue; Lewis, Joshua R.; Xu, Aimin; Levinger, Itamar; Wang, Yu (Frontiers in Endocrinology, 2021)
Objectives: To investigate the serum, plasma and urine levels of lipocalin-2 (LCN2) variants in healthy humans and their associations with risk factors for cardiometabolic (CMD) and chronic kidney (CKD) diseases. Methods: Fifty-nine males and 41 females participated in the study. Blood and urine were collected following an overnight fasting. LCN2 variants were analyzed using validated in-house ELISA kits. Heart rate, blood pressure, lipids profile, glucose, adiponectin, high-sensitivity C-reactive protein (hsCRP), creatinine, cystatin C, and biomarkers for kidney function were assessed. Results: The levels of hLcn2, C87A and R81E in serum and urine, but not plasma, were significantly higher in men than women. Increased levels of LCN2 variants, as well as their relative ratios, in serum and plasma were positively associated with body mass index, blood pressure, triglyceride and hsCRP (P<0.05). No significant correlations were found between these measures and hLcn2, C87A or R81E in urine. However, LCN2 variants in urine, but not plasma or serum, were correlated with biomarkers of kidney function (P<0.05). Conclusions: Both the serum and plasma levels of LCN2 variants, as well as their ratios are associated with increased cardiometabolic risk, whereas those in urine are correlated with renal dysfunction. LCN2 variants represent promising biomarkers for CMD and CKD.